Alternatipathes Molodtsova and Opresko 2017 - Opresko, Dennis M.; Molodtsova, Tina N. (Zenodo, 2021)
Alternatipathes Molodtsova and Opresko, 2017 (emended) Alternatipathes Molodtsova & Opresko, 2017: 358 (see synonymy therein). Diagnosis. Corallum attached to substrate; monopodial, unbranched or with a few basal branches, and pinnulate. When present, pinnate branches of first order develop from lowermost pinnules of stem. Pinnules simple, arranged alternately (including lowermost pair) in two lateral rows. Length of pinnules on stem and branches decreasing in a distal direction, forming a triangularly shaped outline. Striatum absent. Spines conical, smooth, simple (or rarely forked), with acute to slightly rounded apex and flared base. Spines larger on polypar side of pinnule. Polyps 2–7 mm in transverse diameter. Type species. Umbellapathes bipinnata Opresko, 2005. Remarks. The diagnosis of the genus has been emended to account for the larger polyps found in the new species described below. The genus Alternatipathes was established by Molodtsova and Opresko (2017) based on corallum morphology (alternating pinnules and stem lacking a fluted region referred to as a striatum) and the results of mt DNA sequencing studies using cox3-cox1 (Brugler et al. 2013), which indicated that Umbellapathes bipinnata Opresko, 2005, and an undescribed Umbellapathes species (USNM 1204042, see Brugler et al. 2013, figures 2 and 3) were genetically distant from both Bathypathes and Schizopathes . More recent DNA sequencing studies using the mt gene regions, cox3-cox1 and nad5-nad1 (Chery et al. 2018) support the separation of A . bipinnata from Schizopathes however, several unbranched specimens morphologically similar to Alternatipathes grouped with Schizopathes . Further study is needed to determine the parameters that separate Alternatipathes from Schizopathes . Species assigned to the genus. Umbellapathes bipinnata Opresko, 2005, Bathypathes alternata Brook, 1889, Alternatipathes venusta Opresko & Wagner, 2020, and Alternatipathes mirabilis n. sp. Distribution. The genus occurs in the Pacific, Indian, Atlantic and Southern Oceans at depths usually exceeding 2500 m and often greater than 4000 m. Information regarding occurrences in the Southern Ocean (mostly Bellingshausen/Amundsen Abyssal plains) are based on unpublished R/V Eltanin records at the NMNH [e.g., USNM 1114499 (R/V Eltanin sta. 673); USNM 78806 and USNM 83545 (R/V Eltanin sta. 1140); and USNM 78811 (R/V Eltanin sta. 1640)]. : Published as part of Opresko, Dennis M. & Molodtsova, Tina N., 2021, New species of deep-sea Antipatharians from the North Pacific (Cnidaria: Anthozoa: Antipatharia), Part 2, pp. 401-422 in Zootaxa 4999 (5) on page 403, DOI: 10.11646/zootaxa.4999.5.1, http://zenodo.org/record/5119429 : {"references": ["Molodtsova, T. N. & Opresko, D. M. (2017) Black corals (Anthozoa: Antipatharia) of the Clarion-Clipperton Fracture Zone. Marine Biodiversity, 47 (2), 349 - 365. https: // doi. org / 10.1007 / s 12526 - 017 - 0659 - 6", "Opresko, D. M. (2005) New genera and species of antipatharian corals (Cnidaria: Anthozoa) from the North Pacific. Zoologische Mededelingen, Leiden, 79, 129 - 165.", "Brugler, M. R., Opresko, D. M. & France, S. C. (2013) The evolutionary history of the order Antipatharia (Cnidaria: Anthozoa: Hexacorallia) as inferred from mitochondrial and nuclear DNA: implications for black coral taxonomy and systematics. Zoological Journal of the Linnean Society, 169, 312 - 361. https: // doi. org / 10.1111 / zoj. 12060", "Chery, N., Parra, K., Evankow, A., Stein, D., Distel, D., Appiah-Madson, H., Ross, R., Sanon, E., Alomari, N., Johnson, R., Vasovic, A., Horowitz, A., Popa, H., Short, B., Kourehjan, D., Vasquez, D. M., Rodriguez, E., Opresko, D. M. & Brugler, M. R. (2018) Partnering with the Ocean Genome Legacy to advance our understanding of black corals (Order Antipatharia). 15 th Deep-Sea Biology Symposium, Monterey, California, 9 - 14 September 2018. poster presentation. [preprint available from M. Brugler at https: // tidalmarshtaskforce. wixsite. com / uscb / publications]", "Brook, G. (1889) Report on the Antipatharia. Report on the Scientific Results of the Voyage of the HMS Challenger during the years 1873 - 1876, Zoology, 32, 1 - 222.", "Opresko, D. M. & Wagner, D. (2020) New species of black corals (Cnidaria: Anthozoa: Antipatharia) from deepsea seamounts and ridges in the North Pacific. Zootaxa, 4868 (4), 543 - 559. https: // doi. org / 10.11646 / zootaxa. 4868.4.5"]}